Comparative study of caries removal using BRIX 3000 and classic mechanical method - Eftimoska Marina; Petroska Ana; Terzievski Boban; Rendzova Vasilka; Apostolska Sonja (Serbian Medical Society - Dental Section, Belgrade, 2022)
Introduction In dental practice, despite the constant improvement of dental equipment and materials, caries removal using rotational instruments is still not a satisfactory way. The caries removal treatment constantly offers numerous alternatives in order to replace machine tools, and one of them is the chemo-mechanical method. The aim of this paper is to examine the effectiveness of the chemo-mechanical method of caries removal using BRIX 3000 and classic method. Material and Method We used BRIX 3000; a material intended for atraumatic caries removal. Both caries elimination methods were performed in 40 patients with evident carious lesions. Twenty patients underwent atraumatic caries removal while in the other twenty carious tissue was removed using rotating instruments. Results BRIX 3000 was effective in caries removal. A significant reduction in the use of local anesthetics was noticed. Patients did not experience discomfort or pain during treatment with BRIX 3000, but the duration of caries removal using this atraumatic method was significantly longer than with the classic method. Conclusion Atraumatic method of caries removal is an adequate alternative to conventional therapeutic procedures for caries removal, which finds a place in the domain of modern minimally invasive dentistry.